Effect of microwave-assisted processing on quality characteristics of pineapple jam - Mohd Ismail, Nur Aisyah; Abdullah, Norazlin; Muhammad, Norhayati (Penerbit Akademia Baru, 2018)
Traditional heating method of pineapple puree during the production of pineapple jam can cause over degradation of quality of the fresh pineapple. Thus, the objective of this study was to determine optimum microwave-assisted processing conditions for producing pineapple jam which could reduce water activity, and meets minimum requirement for pH and total soluble solids contents of fruit jam. The experiment was designed using full-factorial experimental design, which the power and time of the microwave processing were chosen as the independent variables, while the water activity, pH and total soluble solids (TSS) content of the pineapple jam were determined as dependent variables. The microwave treatment was optimised to achieve ideal properties of pineapple jam. The optimum microwave processing of pineapple jam was obtained at 800 Watts of power for 8 minutes. The usage of domestic microwave oven for the pineapple jam production also results in acceptable pineapple jam with 62% of consumers’ preference compared to conventional fruit jam sold in the marketplace.